CLUSTERING TECHNIQUE TO TEACH WRITING DESCRIPTIVE TEXTS - Yunita, Ita; Sudarsono, Sudarsono; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to examine the effectiveness of clustering technique to teach writing descriptive texts. This research was conducted to Year â€“ 8 students of SMPN 01 Semparuk in Academic Year 2017/2018 by administering a written test before and after the treatments. The researcher applied a pre-experimental design. The population of this research was all of Year â€“ 8 students of SMPN 01 Semparuk in Academic Year 2017/2018, and the sample was taken from Year â€“ 8 Class C which consists of 33 students. The data were analyzed by using t-test and effect size formula. The findings showed that the studentsâ€™ mean score of post-test (72.22) was higher than the studentsâ€™ mean score of pre-test (44.19). On the other hand, the findings also showed that the t-test (16.94) was higher than t-table (1.697) and the effect size (2.88) was categorized as strong effect. In conclusion, the use of clustering technique is significantly effective in teaching writing descriptive texts. Therefore, the alternative hypothesis which stated â€œClustering technique is significantly effective to teach writing descriptive texts to Year â€“ 8 of SMPN 01 Semparuk in Academic Year 2017/2018â€ was accepted.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Key words: Clustering Technique, Teaching Writing, Descriptive Texts, Pre Â Experimental Study